EFFECT OF COMPETENCE, TRAINING AND MOTIVATION ON EMPLOYEE PERFORMANCE (STUDI AT PT. ACE HARDWARE, Tbk, SEMARANG) - Mulyani Mulyani; Hasan Abdul Rozak (Jurnal Ekonomi, 2022)
Employee performance is an action related to the tasks performed by employees and how these actions are performed. Performance is an important element in the company, because performance is an expectation of how a person should behave in carrying out tasks, which means showing a role in the organization. The better the performance of employees in each company, it will affect the company’s goals. Many factors can affect employee performance, such as competence, training and motivation. The purpose of this study was to analyze the effect of competence, training and motivation on employee performance. The population of this research is the employees of PT. Ace Hardware Indonesia Tbk, Semarang, totaling 287 people. With the slovin method, it was obtained a sample of 74 employees. The sampling technique in this study was carried out by a random technique. The types of data used are primary and secondary. The data collection technique used is a questionnaire. The analysis technique used is multiple regression analysis. The results showed that: (1). Competence has a positive effect on employee performance. (2). Training has a positive effect on employee performance. (3). Motivation has a positive effect on employee performance.